Time series (ARIMA) as a tool to predict the temperature-humidity index in the dairy region of the northern desert of Mexico - José Luis Herrera-González; Rafael Rodríguez-Venegas; Martín Alfredo Legarreta-González; Pedro Antonio Robles-Trillo; Ángeles De-Santiago-Miramontes; Darithsa Loya-González; Rafael Rodríguez-Martínez (PeerJ)
The environment in which an animal is situated can have a profound impact on its health, welfare, and productivity. This phenomenon is particularly evident in the case of dairy cattle, then, in order to quantify the impact of ambient temperature (°C) and the relative humidity (%) on dairy cattle, the temperature-humidity index (THI) is employed as a metric. This indicator enables the practical estimation of the stress imposed on cattle by ambient temperature and humidity. A seasonal autoregressive integrated moving average (SARIMA) (4,1,0)(0,1,0)365 model was estimated using daily data from the maximum daily THI of 4 years (2016–2019) of the Comarca Lagunera, an arid region of central-northern Mexico. The resulting model indicated that the THI of any given day in the area can be estimated based on the THI values of the previous four days. Furthermore, the data demonstrate an annual increase in the number of days the THI indicates a risk of heat stress. It is essential to continue building predictive models to develop effective strategies to mitigate the adverse effects of heat stress in dairy cattle (and other species) in the region.